The Impact of the ‘Preparing for the Labour Market’ Status on the Employment Prospects of Older Jobseekers of the Lithuanian Employment Service - Nomeikienė, Inga; Moskvina, Julija (Socialinė teorija, empirija, politika ir praktika, 2026)
A person’s status of ‘preparing for the labour market’ (PPLM) is a new instrument applied by the Employment Service to support individuals facing barriers to labour market participation, with the provision of integrated case management support. Older unemployed people are particularly disproportionately assigned to the status. By employing the semi-structured interviews with older PPLM status holders alongside an analysis of Public Employment Service (PES) statistical data, this paper examines changes in the situation of older (55+) jobseekers following the introduction of the PPLM status. The analysis of normative documents, institutional data, and PES jobseekers’ responses indicates that the meaning and purpose of the status is often misunderstood by its holders, while the limited number of case managers restricts the effective implementation of the intended support model. The availability of PES services and measures for PPLM jobseekers is lower compared to those applicable to the PES jobseekers with the ‘usual’ unemployed status. Thus, the PPLM status can create a risk of further alienation from the labour market for older people.